Distribution differences of macular cones measured by AOSLO: Variation in slope from fovea to periphery more pronounced than differences in total cones. (March 2017) - Elsner, Ann E.; Chui, Toco Y.P.; Feng, Lei; Song, Hong Xin; Papay, Joel A.; Burns, Stephen A.
Highlights: Cone density varies among individuals by more than just a scalar factor. Cone density in the macular center is inversely proportional to the density at 7 deg. Total cones in the retinal can be modelled from the density along 4 meridians. Variation in cone density is greater nearer the fovea. Variation in total cones in the central 14 deg is less variable than for the fovea. Abstract: Large individual differences in cone densities occur even in healthy, young adults with low refractive error. We investigated whether cone density follows a simple model that some individuals have more cones, or whether individuals differ in both number and distribution of cones. We quantified cones in the eyes of 36 healthy young adults with low refractive error using a custom adaptive optics scanning laser ophthalmoscope. The average cone density in the temporal meridian was, for the mean ± SD, 43, 216 ± 6039, 27, 466 ± 3496, 14, 996 ± 1563, and 12, 207 ± 1278 cones/mm 2 for 270, 630, 1480, and 2070 μm from the foveal center. Cone densities at 630 μm retinal eccentricity were uncorrelated to those at 2070 μm, ruling out models with a constant or proportional relation of cone density to eccentricity. Subjects with high central macula cone densities had low peripheral cone densities. The cone density ratio (2070:630 μm) was negatively correlated with cone density at 630 μm, consistent with variations in the proportion of peripheral cones migrating towards the center. We modelled the total cones within a central radius of 7 deg, using the temporal data and our published cone densities for temporal, nasal, superior, and inferior meridians. We computed an average of 221, 000 cones. The coefficient of variation was 0.0767 for total cones, but higher for samples near the fovea. Individual differences occur both in total cones and other developmental factors related to cone distribution.